2019
DOI: 10.1016/j.ijrobp.2019.06.1660
|View full text |Cite
|
Sign up to set email alerts
|

High-grade Radiologic Extra-nodal Extension Predicts Distant Metastasis in Stage II Nasopharyngeal Carcinoma

Abstract: and were given a second course of radiotherapy. The median follow-up period was 47.7 months (1.8 to 110.6) measured from the start of the reirradiation. IMRT of various types including conventional fractionation scheme, stereotactic radiotherapy, twice-daily (BID) radiation were used to deliver the second course of radiotherapy. The prescribed doses delivered from the different fractionation schemes were converted into Equivalent Dose at 2 Gy per fractions (EQD2) using a/b ratios of 10 Gy and 3 Gy for the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…12 A previous study in NPC demonstrated that nodal matting was a high-grade ENS, which could significantly influence the survival outcomes in Stage II NPC patients. 18 In our study, we confirmed the adverse prognostic value of nodal matting for DMFS in NPC patients, while all ENS was not an independent risk factor for DMFS. Therefore, we believe that nodal matting was associated with but different from all ENS.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…12 A previous study in NPC demonstrated that nodal matting was a high-grade ENS, which could significantly influence the survival outcomes in Stage II NPC patients. 18 In our study, we confirmed the adverse prognostic value of nodal matting for DMFS in NPC patients, while all ENS was not an independent risk factor for DMFS. Therefore, we believe that nodal matting was associated with but different from all ENS.…”
Section: Discussionsupporting
confidence: 78%
“…11,15,17 A large number of cervical lymph node metastases often occur in patients with NPC, and nodal matting can be observed on MRI in many of these cases. 18 However, the prognostic value of nodal matting in NPC is not clear. In this study, the incidence of nodal matting was 24.6% in patients with NPC, which was comparable to that of 16-27% in cases of oropharyngeal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations